Вікові варіації геомагнітного поля на літосфернихплитах Землі - Сумарук, П.В.; Сумарук, Т.П. (Геофизический журнал, 2018)
Исследована зависимость величины знака вековых вариаций геомагнитного поля, очищенных от 3- и 11-летних составляющих, от положения обсерваторий на тектонических плитах. Для исследования были выбраны обсерватории, имеющие длинные ряды наблюдений. The dependence of the value and sign of the geomagnetic secular variations (SV) refined of 3- and 11-year components on the position of observatories at different tectonic plates is investigated. The observatories of the long row observations were used for the studies.